Evaluasi Sistem Angkutan Sampah Kota Kandangan Dengan Pemanfaatan Sistem Informasi Geografis - Rahmat Hidayat (Department of Urban and Regional Planning, Diponegoro University, 2013)
An existing Kandangan City solid waste transportation system has not been able to handle solid waste that occurs, the level of service in the year 2010 about 40%, it is still far from the minimum standard set is 60%. To evaluate the Kandangan City solid waste transport system assisted with software ArcGIS 10 from ESRI. Solid waste generation identification results Kandangan City is 56096.67 liters/day, which is still dominated by the composition of the household resources by 71.93%, but it also acquired 93 new pieces of candidates waste bin location. Then the analysis of bin location suitability of the 26 existing bin location and 93 new bin location produce 61 optimal bin location. Further analysis of the 3 pieces of existing solid waste transportation routes only 1 solid waste transportation route that need to be repaired is DA968AM. From the analysis of the optimal and route obtained 7 sets of transportation routes using 3 units of dump trucks. Level of service with well-managed solid waste generation indicator is 65.03%, an increase of 25% compared to the existing condition which is only 40%, in addition to compliance with service level Minimum Service Standart fields of solid waste. Based on the analysis results can be concluded evaluation of Kandangan City solid waste transportation system with the use of GIS can improve the service level solid waste management.